2015
DOI: 10.2527/jas.2015-9424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral meloxicam administration to beef cattle receiving lipopolysaccharide administration or vaccination against respiratory pathogens1

Abstract: This study evaluated the effects of oral meloxicam administration on metabolic, inflammatory, and acute-phase responses of beef cattle receiving a lipopolysaccharide (LPS) challenge (Exp. 1; d -1 to 6) or vaccinated against respiratory pathogens (Exp. 2; d 7 to 21). Twenty-one Angus steers ( = 11) and heifers ( = 10) were housed in individual pens on d -15 and were offered free-choice water, mineral-vitamin mix, and hay until d 21. In Exp. 1, cattle were ranked on d -1 by sex and BW and assigned to 1) oral mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…These include synthesis of proinflammatory cytokines, such as TNFα from leukocytes, and a subsequent increase in body temperature and hepatic synthesis of acute phase proteins including haptoglobin (Carroll and Forsberg, 2007). Accordingly, time effects (P < 0.01) were detected for vaginal temperature, serum TNFα, and serum haptoglobin during the LPS challenge period (Figure 3), indicating that LPS administration elicited the expected innate immune responses (Carroll and Forsberg, 2007) as reported by others (Carroll et al, 2009;Rodrigues et al, 2015). In addition, a treatment × hour interaction was detected (P = 0.03) for serum TNFα concentration, which was greater (P ≤ 0.04) for OMN-supplemented cows compared with CON cows at 1, 2, and 3 h relative to LPS administration (Figure 3).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…These include synthesis of proinflammatory cytokines, such as TNFα from leukocytes, and a subsequent increase in body temperature and hepatic synthesis of acute phase proteins including haptoglobin (Carroll and Forsberg, 2007). Accordingly, time effects (P < 0.01) were detected for vaginal temperature, serum TNFα, and serum haptoglobin during the LPS challenge period (Figure 3), indicating that LPS administration elicited the expected innate immune responses (Carroll and Forsberg, 2007) as reported by others (Carroll et al, 2009;Rodrigues et al, 2015). In addition, a treatment × hour interaction was detected (P = 0.03) for serum TNFα concentration, which was greater (P ≤ 0.04) for OMN-supplemented cows compared with CON cows at 1, 2, and 3 h relative to LPS administration (Figure 3).…”
Section: Resultssupporting
confidence: 59%
“…= 38). However, serum haptoglobin concentration was only greater (P ≤ 0.05) in OMN-supplemented versus CON cows from 36 to 72 h after LPS challenge ( Figure 3), when serum haptoglobin is expected to peak upon LPS administration (Rodrigues et al, 2015), although the treatment × hour interaction was not significant (P = 0.50). Supporting our results, Sanchez et al (2012) and Burdick Sanchez et al (2014) also reported increased acute phase reaction in beef cattle supplemented with OMN and receiving LPS administration.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Richeson et al (2009) examined the effect of vaccine administration immediately following transportation, and reported that anti-BVDV type I Ab reached a high titer sooner than animals vaccinated after 14 days, without compromising average daily weight gain or growth. Other investigations also confirm our findings that MEL did not affect vaccination response to respiratory pathogens (Rodrigues et al, 2015).…”
Section: Discussionsupporting
confidence: 90%